2005
DOI: 10.1016/j.jallcom.2004.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Site preference of ternary alloying additions to NiTi: Fe, Pt, Pd, Au, Al, Cu, Zr and Hf

Abstract: Atomistic modeling of the site substitution behavior of Pd in NiTi (J. Alloys and Comp. (2004), in press) has been extended to examine the behavior of several other alloying additions, namely, Fe, Pt, Au, Al, Cu, Z r and Hf in this important shape memory alloy. It was found that all elements, to a varying degree, displayed absolute preference for available sites in the deficient sublattice. However, the energetics of the different substitutional schemes, coupled with large scale simulations indicate that the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 13 publications
3
36
0
Order By: Relevance
“…This is a positive indication of strong directional bonding leading to brittleness in (B19/B19') phase. The present theoretical values of heat of formation of TiX alloys tend to increase systematically as we go from 3d to 4d to 5d metals [22]. From Figure 8 we observe the heat of formation increases from TiFe to TiNi and then to TiPd.…”
Section: Cohesive Energy and Heat Of Formationsupporting
confidence: 50%
“…This is a positive indication of strong directional bonding leading to brittleness in (B19/B19') phase. The present theoretical values of heat of formation of TiX alloys tend to increase systematically as we go from 3d to 4d to 5d metals [22]. From Figure 8 we observe the heat of formation increases from TiFe to TiNi and then to TiPd.…”
Section: Cohesive Energy and Heat Of Formationsupporting
confidence: 50%
“…Therefore, a wide range of Sc solubility is expected in TiNiPd without second-phase formation. (2) According to currently unpublished atomistic simulations for quaternary additions to TiNiPd by Bozzolo, performed in a similar manner to the ternary additions studied by Bozzolo et al in TiNi [24] and TiPd and TiPt, [25] Sc was found to have a significant effect on the formation energy of TiNiPd, increasing the formation energy for a given unit of alloying addition more than any other element studied. Therefore, it can be inferred that Sc significantly affects the bond strength in the alloy, which may affect both the transformation and slip behavior.…”
Section: Introductionmentioning
confidence: 83%
“…The strong influence of Pd on the transformation characteristics and lattice parameters and thus l 2 can be rationalized by the substitution behavior of Pd, which is known to occupy Ni sites, irrespectively of concentration, [22] and has a comparatively larger atomic volume. In contrast, Cu atoms show no site preference [22] and have comparable atomic volume to that of Ni. Thus, for additions of Cu, the sensitivity of DT to l 2 is nearly one order of magnitude smaller than that for Pd.…”
Section: Full Papermentioning
confidence: 99%